Pengungkapan Emisi Karbon: Studi Pada Perusahaan Manufaktur di Indonesia - B1031141032, Desianti Guntari (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACT CARBON EMISSION DISCLOSURE: STUDY AT MANUFACTURING COMPANY IN INDONESIADESIANTI GUNTARIB1031141032 Carbon emission disclosure is a diclosure to assess an organization’s carbon emissions and set targets for reduction. This study aimed to analyze and provide empirical evidence about the impact of firm size, profitability, growth, and environmental performance toward carbon emission disclosure of manufacturing companies in Indonesia. The method that was used to measure the extent of carbon emission disclosure adopted the checklist that was developed based on the information request sheet provided by Carbon Disclosure Project. This research applied purposive sampling method to obtain 15 manufacturing company that listed in Indonesia Stock Exchange (BEI) during 2015-2017. Research data is a secondary data derived from company’s annual and sustainability reports and the hypothesis is tested using multiple regression analysis. The results of this study indicate that firm size have a significant effect on the extent of carbon emission disclosure, however the other factors, such as profitability, growth, and environmental performance have no significant effect to the extent of carbon emission disclosure.Keywords: Carbon  Emission, Carbon Emission Disclosure, Global Warming, Voluntairy Disclosure, Carbon AccountingDAFTAR PUSTAKA Undang-Undang Republik Indonesia Nomor 17 Tahun 2004 tentang Pengesahan Kyoto Protocol to the United Nations Framework Convention On Climate Change (Protokol Kyoto atas Konvensi Kerangka Kerja Perserikatan Bangsa-Bangsa tentang Perubahan Iklim).Undang-Undang Republik Indonesia Nomor 40 Tahun 2007 tentang Perseroan Terbatas.Perpres No. 61 tahun 2011 mengenai Rencana Aksi Nasional Penurunan Emisi Gas Rumah Kaca.Perpres No. 71 tahun 2011 mengenai Penyelenggaraan Inventasrisasi Gas Rumah Kaca Nasional.Ahmad, Z., Hassan, S., & Mohammad, J. 2003. Determinants of Environmentl Reporting in Malaysia. International Journal of Business Studies, No. 11.Almilia, Luciana Spica. 2009. Analisa Kualitas Isi Financial and Sustainability Reporting Pada Website Perusahaan Go Publik di Indonesia. Seminar Nasional Aplikasi Teknologi Informasi 2009 (SNATI 2009) ISSN: 1907-5022. Yogyakarta, 20 Juni.Choi, B. B., Lee, D., & Psaros, J. 2013. An Analysis of Australian Company Carbon Emission Disclosures. Pasific Accounting Review, Vol. 25.Deegan, C., Rankin, M., & Tobin, J, 2002. An Examination of The Corporate Social and Environmental Disclosures of BHP from 1983-1997: A Test of Legitimacy Theory. Accounting, Auditing & Accountability Journal. No. 15.Elkington, J. 1997, Cannibal with Forks The Triple Bottom Line of 21st Century Business. Oxford: Capstone Publishing Limited.Freedman, M., & Jaggi, B. 2005. Global Warming, Commitment to the Kyoto Protocol, and Accounting Disclosures by The Largest Global Public Firms from Polluting Industries. The International Journal of Accounting. No. 20.Ghozali, I., & Chariri, A. 2007. Teori Akuntansi (Vol. 3). Semarang: Badan Penerbit Universitas Dipenogoro.Jannah, Richatul, dan Dul Muid. 2014. Analisis Faktor-Faktor yang Mempengaruhi Carbon Emission Disclosure pada Perusahaan di Indonesia (Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia Periode 2010-2012). Dipenogoro Journal of Accounting, Vol. 3, No. 2.Luo, L., Lan, Y.-C.,  Tang, Q. 2013. Comparison of Propensity for Carbon Disclosure Between Developing and Developed Countries. Accounting Research Journal, Vol. 26.Pradini, Harlinda Siska. 2013. The Analysis of Information Content towards Greenhouse Gas Emissions Disclosure in Indonesia Companies. Universitas Dipenogoro, Indonesia.Prado-Lorenzo, J.-M, Rodriguez-Dominguez, L., Gallego-Alvarez, I., & Garcia-Sanchez, I.-M. 2009. Factors Influencing The Disclosure of Greenhouse Gas Emissions in Companies World-Wide. Management Decision. No. 47.Ratnatunga, J. 2007. Carbon Cost Acconting: The Impact of Global Warming on the Cost Accounting Profession. Journal of Applied Management Accounting Research. No. 5.Sartono, A. 2001. Manajemen Keuangan Teori dan Aplikasi. Yogyakarta: BPFE.Situmeang, Ilona V. O. 2016. Corporate Social Responsibility: Dipandang dari Perspektif Komunikasi dan Organisasi. Yogyakarta: Ekuilibria.Titman, S., & Trueman, B. 1986.. Information Quality and The Valuation of New Issues. Journal of Accounting and Economics. No. 8.United Nations Framework Convention on Climate Change (UNFCC). 1998. Kyoto Protocol to The United Nations Framework Convention on Climate Change.IPCC. 2007. Intergovernmental Panel on Climate Change. Diunduh di http://www.ipcc.ch/.